Review of child Second Language Aquisition (SLA): Examining Theories and Research - Oliver, Rhonda; Azkarai, A. (2017)
Within the field of second language acquisition (SLA), there has been much less research undertaken with children than with adults, yet the two cohorts are quite distinct in characteristics and in their learning processes. This article provides a review of child SLA research, particularly the research with a pedagogical focus. We describe a series of studies, including those informed by different theoretical perspectives (interactionist and sociocultural), in different instructional settings (i.e., second language, foreign language, immersion, and content and language integrated learning [CLIL] contexts) and using different research methodologies (longitudinal, case study, experimental, and naturalistic). We begin by highlighting the importance of age as a factor in SLA research, presenting studies that have focused on the differences existing between younger and older learners. We also consider interventions that can support language learning—including form-focused instruction and the use of tasks. We finish by presenting a proposed change in the way that research with children is conducted.